THE IMPACT OF PANCASILA AS THE STATE IDEOLOGY OF INDONESIA TOWARD THE PROVISION ON DEATH PENALTY IN THE PENAL CODE BILL - Munthe, Cesar Antonio; Soge, Paulinus (Justitia et Pax, 2018)
Pancasila has been the state ideology of Indonesia since the day after the independence of Indonesia that is on the 18th of August 1945. It was formulated by our founding fathers by taking our own values and cultures inherited by our ancestors from some old kingdomsÂ  such as Kutai in Kalimantan, Sriwijaya in Sumatra, and Majapahit in Java. One year after the independenceÂ  on the 17th of August 1945, Indonesian government promulgated Law No. 1 Year 1946 concerning The Penal Code on 26th Â of Â February 1946. Through this law the government at that time stated that Wetboek van Strafrecht voor Nederlandsch-IndieÂ  (W.v.S. Ned. Indie (S. 1915 No. 732) as the main written penal code and was formally calledÂ  Kitab Undang-undang Hukum Pidana (KUHP) which in Article 10 provides death penalty as the heaviest main punishment. Dealing with that provision there has been a long debate among Indonesian people whether death penalty is in accordance with Pancasila or not. Netherlands as the home base of death penalty dropped it out from its penal code in 1870 because of the strong struggle of human right proponents. In Indonesia a research carried out in 1981/1982 by The Law Faculty of Undip collaborating with theÂ  The Supreme Court Â found out that both proponents and opponents of death penalty used Pancasila as â€œjustificationâ€. Â In the effort to give respect to both parties Â legal drafters of theÂ  Penal Code Bill provide death penalty as â€œspecific punishmentâ€ and put it out of the main punishment Â in the Penal Code Bill.Key Words: Pancasila, State ideology, Legal drafters, Specific punishment, The Penal Code Bill.